Osteoprotegerin mediates adipogenesis in obesity - Lyu, Zipan (2024)
Introduction: Adipogenesis, the process of white adipose tissue expansion, plays a critical role in the development of obesity. Osteoprotegerin (OPG), known for its role in bone metabolism regulation, emerges as a potential regulator in mediating adipogenesis during obesity onset. Objectives: This study aims to elucidate the involvement of OPG in adipogenesis during the early phases of diet-induced obesity and explore its therapeutic potential in obesity management. Methods: Using a diet-induced obesity model, we investigated OPG expression patterns in adipocytes and explored the mechanisms underlying its involvement in adipogenesis. We also assessed the effects of targeted silencing of OPG and recombinant OPG administration on obesity progression and insulin resistance. Additionally, the impact of electroacupuncture treatment on OPG levels and obesity management was evaluated in both animal models and human participants. Results: OPG expression was prominently activated in adipocytes of white adipose tissues during the early phase of diet-induced obesity. Hyperlipidemia induced Cbfa1-dependent OPG transcription, initiating and promoting adipogenesis, leading to cell-size expansion and lipid storage. Intracellular OPG physically bound to RAR and released the PPARɤ/RXR complex, activating adipogenesis-associated gene expression. Targeted silencing of OPG suppressed obesity development, while recombinant OPG administration promoted disease progression and insulin resistance in obese mice. Electroacupuncture treatment suppressed obesity development in an OPG-dependent manner and improved obesity parameters in obese human participants. Conclusion: OPG emerges as a key regulator in mediating adipogenesis during obesity development. Targeting OPG holds promise for the prevention and treatment of obesity, as evidenced by the efficacy of electroacupuncture treatment in modulating OPG levels and managing obesity-related outcomes.